Isolation of Mutants With Reduced Susceptibility to Piperaquine From a Mutator of the Rodent Malaria Parasite Plasmodium berghei - Ikeda, Mie; Hirai, Makoto; Tachibana, Shin-Ichiro; Mori, Toshiyuki; Mita, Toshihiro (Frontiers in Cellular and Infection Microbiology, 2021)
Elucidation of the mechanisms of drug resistance in malaria parasites is crucial for combatting the emergence and spread of resistant parasites, which can be achieved by tracing resistance-associated mutations and providing useful information for drug development. Previously, we produced a novel genetic tool, a Plasmodium berghei mutator (PbMut), whose base substitution rate is 36.5 times higher than that of wild-type parasites. Here, we report the isolation of a mutant with reduced susceptibility to piperaquine (PPQ) from PbMut under PPQ pressure by sequential nine-cycle screening and named it PbMut-PPQ-R-P9. The ED50 of PbMut-PPQ-R-P9 was 1.79 times higher than that of wild-type parasites, suggesting that its PPQ resistance is weak. In the 1st screen, recrudescence occurred in the mice infected with PbMut but not in those infected with wild-type parasites, suggesting earlier emergence of PPQ-resistant parasites from PbMut. Whole-genome sequence analysis of PbMut-PPQ-R-P9 clones revealed that eight nonsynonymous mutations were conserved in all clones, including N331I in PbCRT, the gene encoding chloroquine resistance transporter (CRT). The PbCRT(N331I) mutation already existed in the parasite population after the 2nd screen and was predominant in the population after the 8th screen. An artificially inserted PbCRT(N331I) mutation gave rise to reduced PPQ susceptibility in genome-edited parasites (PbCRT-N331I). The PPQ susceptibility and growth rates of PbCRT-N331I parasites were significantly lower than those of PbMut-PPQ-R-P9, implying that additional mutations in the PbMut-PPQ-R9 parasites could compensate for the fitness cost of the PbCRT(N331I) mutation and contribute to reduced PPQ susceptibility. In summary, PbMut could serve as a novel genetic tool for predicting gene mutations responsible for drug resistance. Further study on PbMut-PPQ-R-P9 could identify genetic changes that compensate for fitness costs owing to drug resistance acquisition.